Analisis Koneksi Matematis Siswa dalam Menyelesaikan Soal Setara TIMSS Ditinjau dari Locus of Control - Sutrisno, Nurul Auliyah; Pambudi, Didik Sugeng; Martikusuma, Randi Pratama (Edumatika, 2020)
This study aims to describe the students’ mathematical connections in terms of the locus of control. The mathematical connection indicators in this study are writing down the mathematical concepts that underlie the answers, recognize the relationship of various mathematical ideas and mathematical topics that can be related to problems of everyday life, and understand how to solve mathematical ideas that are interrelated and underlie each other to obtain an integrated whole. Data collection methods in this study were questionnaires, tests, and interviews. The subjects of this study were six seventh-grade students at MTs Negeri 7 Jember. The data analyzed by qualitative descriptive analysis. Based on the tests and interviews analysis, we known that students with internal locus of control could write mathematical concepts as a two variable linear equation system (TVLES). Students can connect TVLES material with problems, for example, represented the object in variables x and y. Students can also solved the problems related to TVLES material by using common examples, elimination and substitution methods. While the students’ with external locus of control also can write the mathematical concepts as a TVLES. But the students did not write in detail the relationship between TVLES material and the problem. Students can not solve problems by using TVLES solutions such as elimination and substitution, but students only use estimates in finding solutions.